การคำนวณเงินสำรองสำหรับการประกันภัยรถยนต์โดยใช้ตัวแบบคอปปูลา - เมธิณี เลิศวิระยะไพบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
There are many standard methods to calculate the reserve estimation, Chain Ladder method is one of the standard methods but it does has some drawbacks as the data compilation of this method does not cover both delay time and covatiate factors which have an impact on reserve estimation. This thesis shows method of reserve estimation for automobile insurance claim payment by Semi-survival copula model and compares its result with Chain-Ladder method. Data used are claim records during 2007 to 2009 of comprehensive automobile insurance policy which comprise of sedan, passenger car and truck from one of a non-life insurance company in Thailand. The result of this study has shown that reserve estimation of automobile insurance policy by Semi-survival copula model decreases when the level of parameter in Clayton copula function increases. The estimation of reserve using estimated parameter in Clayton copula function from Kendall’s tau coefficient which is a relationship of delay time, is less than estimation reserve using Chain-Ladder method.